The democratic process and the market : challenges of the transition - Simai, Mihály (United Nations University Press, 1999)
This text provides a regional perspective on the interrelationship between political and economic change, and delineates the challenges that these developments present to the former socialist countries of East and Central Europe, undergoing a transition to democracy in the 1990s.